login
This site is supported by donations to The OEIS Foundation.

 

Logo


Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A000904 a(n) = (n+1)*a(n-1) + (n+2)*a(n-2) + a(n-3); a(1)=0, a(2)=3, a(3)=13.
(Formerly M2955 N1193)
7
0, 3, 13, 83, 592, 4821, 43979, 444613, 4934720, 59661255, 780531033, 10987095719, 165586966816, 2660378564777, 45392022568023, 819716784789193, 15620010933562688, 313219935456042955, 6593238655510464741 (list; graph; refs; listen; history; text; internal format)
OFFSET

1,2

COMMENTS

Numbers connected with the ménage problem (cf. A000179).

REFERENCES

N. J. A. Sloane, A Handbook of Integer Sequences, Academic Press, 1973 (includes this sequence).

N. J. A. Sloane and Simon Plouffe, The Encyclopedia of Integer Sequences, Academic Press, 1995 (includes this sequence).

LINKS

T. D. Noe, Table of n, a(n) for n=1..100

E. Lucas, Théorie des Nombres, Gauthier-Villars, Paris, 1891, Vol. 1, p. 495.

E. Lucas, Théorie des Nombres, Gauthier-Villars, Paris, 1891, Vol. 1. [Annotated scan of pages 488-499 only]

FORMULA

G.f.: 1/(x+x^2)^2*Sum_{n>=0} n!*(x/(1+x)^2)^n. - Vladeta Jovovic, Jun 29 2007

G.f.: (1/E(0)-1+x-x^2)/x^2 where E(k)= (1+x)^2 + k*x - (k+1)*x*(1+x)^2/E(k+1); (continued fraction, Euler's 1st kind, 1-step). - Sergei N. Gladkovskii, Sep 17 2012

From Vladimir Shevelev, Jun 29 - Jul 22 2015: (Start)

Using formulas in [Lucas], we have

(i) a(1)=0, a(2)=3, for n>=3, a(n) = (n+2)*a(n-1) + a(n-2) + 2*(-1)^n

(Note that (i) yields a(3)=13 and, for n>=4,

a(n-1) = (n+1)*a(n-2) + a(n-3) - 2*(-1)^n. Summing this with (i), we see that (i) defines A000904);

(ii) for n>=1, a(n) = (A000179(n+3) + 2*(-1)^n)/(n+3);

(iii) for n>=3, a(n) = a(n-2) + A000179(n+2);

(iii)*  if n is even, then a(n) = Sum_{i=0..(n+2)/2)}A000179(2*i);

(iii)** if n is odd, then a(n) = Sum_{i=2..(n+1)/2} A000179(2*i+1).

Also

(iv)  a(n+1) = A000271(n+3) - a(n);

(iv)*  a(n) = Sum_{i=0..n+2}(-1)^i*A000271(n-i+2);

(v) a(n-2) = Sum_{i=0..n}(-1)^i*binomial(2*n-i+1, i)*(n-i)!, n>=3.

Note that Lucas considered this sequence with other initials. His formulas (i) - (iii), which he proved on pp. 491-495 of his book [Lucas], we wrote for the current initials.

The other 5 formulas, including the explicit formula 5), are new and we give their proofs:

(iii)*,(iii)**. Formulas (iii)* and (iii)** are obtained by the direct summation of (iii) over even and odd values respectively, taking into account the initials.

(iv). To obtain (iv), write (iii) in the form

a(j+1) - a(j) = -(a(j) - a(j-1)) +  A000179(j+3), j>=2.

Summing Sum_{j=2..n}, we have

a(n+1) - a(2) = -a(n) + a(1) + Sum_{j=2..n}A000179(j+3). Since a(1)=0, a(2)=3, we find

a(n+1)-3 = -a(n) + Sum_{i=5..n+3}A000179(i). But A000179(3)=1, A000179(4)=2. Therefore, we have

a(n+1) = -a(n) + Sum_{i=3..n+3}A000179(i).

It is left to note that, by the definition,

A000271(n) = Sum{i=3..n}A000179(i). So

a(n+1) = A000271(n+3) - a(n).

(iv)*. In view of the first four initials 1,0,0,1 of A000271, we have

Sum_{i=0..n+2}(-1)^i*A000271(n-i+2) = Sum_{i=0..n-2}(-1)^i*A000271(n-i+2) and, by (iv), the last sum equals

Sum_{i=0..n-2}(-1)^i(a(n-i)+a(n-i-1)) = a(n) + (-1)^(n-2)*a(1) = a(n).

(v). We use induction for n>=3. In case n=3 (v) gives 6-6*2+10-4=0 = a(1). Set n:=n+2.

Suppose for some (now n>=1) we have

a(n) = Sum_{i=0..n+2}(-1)^i*binomial(2*n-i+5, i}*(n+2-i)!                           (*)

Further we use (iv). In A259212 we proved an explicit formula for A000271(n-1) such that we have

A000271(n+3) = Sum_{j=0..n+3}(-1)^j * binomial(2*n-j+6,j)*(n-j+3)!, n>3.

Now, by (iv) and (*) with changing summing j=i+1, we have

a(n+1) = Sum_{j=0..n+3}(-1)^j * binomial(2*n-j+6,j)*(n-j+3)! + Sum_{j=1..n+3}(-1)^j* binomial(2*n-j+6, j-1}*(n+3-j)!

Since binomial(n,-1)=0, then in the second sum the summing could begin with j=0.

So, we have

a(n+1) = Sum_{j=0..n+3}}(-1)^j* binomial(2*n-j+7, j}*(n+3-j)! = Sum_{j=0..n+3}(-1)^j* binomial(2*(n+1)-j+5,j)*((n+1)+2-j)!

Thus this expression formally is obtained from (*) by replacing n with n+1.

QED (End)

a(n) ~ n! * n^2 / exp(2). - Vaclav Kotesovec, Jul 04 2015

EXAMPLE

G.f. = 3 x^2 + 13 x^3 + 83 x^4 + 592 x^5 + 4821 x^6 + 43979 x^7 + 444613 x^8 + ...

MATHEMATICA

max = 19; f[x_] = 1/(x+x^2)^2 * Sum[ n!*(x/(1+x)^2)^n, {n, 0, max+2}]; Series[ f[x]+1/x-1/x^2, {x, 0, max}] // CoefficientList[#, x]& // Rest (* Jean-François Alcover, May 16 2013, after Vladeta Jovovic *)

RecurrenceTable[{a[1]==0, a[2]==3, a[3]==13, a[n]==(n+1)a[n-1]+(n+2)a[n-2]+a[n-3]}, a, {n, 20}] (* Harvey P. Dale, Aug 03 2016 *)

PROG

(Haskell)

a000904_list = 0 : 3 : 13 : zipWith (+) a000904_list

   (zipWith (+) (zipWith (*) [6..] $ drop 1 a000904_list)

                (zipWith (*) [5..] $ drop 2 a000904_list))

-- Reinhard Zumkeller, Nov 22 2011

CROSSREFS

Cf. A000179, A000271.

Sequence in context: A057993 A208810 A219906 * A201304 A173998 A135743

Adjacent sequences:  A000901 A000902 A000903 * A000905 A000906 A000907

KEYWORD

nonn,nice,easy

AUTHOR

N. J. A. Sloane

EXTENSIONS

More terms from Larry Reeves (larryr(AT)acm.org), Nov 27 2001

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified October 22 14:53 EDT 2018. Contains 316490 sequences. (Running on oeis4.)